(untitled) (Global Journal of Science Frontier Research, 2023)
The study analyses risk management strategies among poultry enterprises in Akwa Ibom State Nigeria Multistage sampling technique was to select 122 poultry farmers for the study Data obtained were analyzed using descriptive inferential statistics and maximum likelihood estimates Results of the study revealed that majority 54 9 were male with a mean age of 49 years